A population‐based cost description study of oral treatment of hospitalized Western Australian children aged younger than 15 years. (3rd March 2015) - Alsharif, Alla Talal; Kruger, Estie; Tennant, Marc
Abstract Objectives We sought to analyze the economic cost of a decade of dental hospital admissions in Western Australian children under the age of 15 years and to identify socio‐demographic characteristics associated with these costs. Methods This study analyzed the cost of 43, 937 child patients under the age of 15 years hospitalized for an oral health–related condition, as determined by principal diagnosis International Classification of Diseases (ICD‐10AM). The Australian Refine Diagnosis Related Group version 5.1 was used to calculate the direct cost. An analysis of costs was broken down by socioeconomic status, primary place of residency, age, gender, insurance status, and Indigenous status. Results The total DRG cost of these admissions was approximately AUS$92 million million over 10 years. Most of these funds went toward treating "Dental caries" and "Embedded and impaction" conditions of children under the age of 15 years. Approximately 95 percent of the total cost of hospitalization for oral conditions, over the last decade, accounted for non‐Indigenous children. Since 2000, the direct cost of child hospitalization for oral‐related conditions has increased to reach $13 million AUD in 2009. Conclusions This study identified the substantial economic burden of child oral‐related hospitalizations that emphasizes the importance of preventing costly inpatient treatments.